Acute kidney injury in cardiogenic shock: definitions, incidence, haemodynamic alterations, and mortality - Tarvasmäki, Tuukka; Haapio, Mikko; Mebazaa, Alexandre; Sionis, Alessandro; Silva‐Cardoso, José; Tolppanen, Heli; Lindholm, Matias Greve; Pulkki, Kari; Parissis, John; Harjola, Veli‐Pekka; Lassus, Johan; Banaszewski, Marek; et al. (European journal of heart failure, 2018)
Aims To investigate the incidence, haemodynamic alterations and 90‐day mortality of acute kidney injury (AKI) in patients with cardiogenic shock. We assessed the utility of creatinine, urine output (UO) and cystatin C (CysC) definitions of AKI in prognostication. Methods and results Cardiogenic shock patients with serial plasma samples (n = 154) from the prospective multicenter CardShock study were included in the analysis. Acute kidney injury was defined and staged according to the KDIGO criteria by creatinine (AKIcrea) and/or UO (AKIUO). CysC‐based AKI (AKICysC) was defined similarly to AKIcrea. Changes in haemodynamic parameters were assessed over time from baseline until 96 h. Mean age of the study population was 66 ± 12 years and 74% were men. Median baseline creatinine was 1.12 [interquartile range (IQR) 0.87–1.54] mg/dL and CysC 1.19 (IQR 0.90–1.69) mg/L. The 90‐day mortality was 38%. The incidences for AKI were: AKIcrea 31%, AKIUO 50%, and AKICysc 33%. AKIcrea [odds ratio (OR) 12.2, 95% confidence interval (CI) 4.1–36.0] and AKICysC (OR 2.5, 95% CI 1.1–6.1), but not AKIUO, were independent predictors of mortality. However, a stricter UO cut‐off of <0.3 mL/kg/h for 6 h was independently associated with 90‐day mortality (OR 3.6, 95% CI 1.4–9.3). Development of AKI was associated with persistently elevated central venous pressure and decreased cardiac index and mean arterial pressure. Conclusions Acute kidney injury is frequent in patients with cardiogenic shock and especially AKIcrea predicts poor outcome. The KDIGO UO criterion seems, however, rather liberal and a stricter AKI definition of UO <0.3 mL/kg/h for at least 6 h seems more useful for mortality risk prediction. Haemodynamic alterations reflecting venous congestion and hypoperfusion were associated with AKI.